Hypoglycemia and associated comorbidities among newborns of mothers with diabetes in an academic tertiary care center - Bamehrez, Maha (Frontiers in Pediatrics, 2023)
Background Hypoglycemia is considered the common metabolic problem in newborns with serious long-term sequelae. This study evaluates the incidence of hypoglycemia in the newborns of mothers with diabetes mellitus and assesses the comorbidities that affect the newborns of mothers with gestational diabetes compared with the newborns of mothers with pregestational diabetes mellitus. Methods This retrospective cohort study was conducted between January-2018 and December-2020. All admissions to the hospital nursery of the newborns of diabetic mothers with diabetes mellitus were included. Results The study comprised 1,036 mothers with diabetes, of the newborns of mothers with pregestational diabetes, 22% had hypoglycemia, and of mothers with gestational diabetes, 12%. Mothers with pregestational diabetes had a significantly higher risk of needing an emergency cesarean section (OR: 2.1, 95% CI: 1.3–3.4); and of having a baby who is large for its gestational age (OR: 9.5, 95% CI: 2.6–35.5), must be admitted to the NICU (OR: 2.9, 95% CI: 1.5–5.6), has respiratory distress syndrome (OR: 3.3, 95% CI: 1.5–7.4), and needs gavage feeding (OR: 3.5, 95% CI: 1.4–8.9). Conclusion About 13% of the newborns of mothers with diabetes had hypoglycemia. Significantly more of these newborns were of mothers with pregestational diabetes than of mothers with gestational diabetes. Newborn of mothers with pregestational diabetes mellitus have the risk of large weight and neurological problems, such as sucking difficulties, length of hospital stay, NICU admission, and respiratory distress syndrome.